2015
DOI: 10.1111/1462-2920.12856
|View full text |Cite
|
Sign up to set email alerts
|

Diguanylate cyclase DgcP is involved in plant and human Pseudomonas spp. infections

Abstract: SummaryThe second messenger cyclic di-GMP controls the transition between different lifestyles in bacterial pathogens. Here, we report the identification of DgcP (diguanylate cyclase conserved in Pseudomonads), whose activity in the olive tree pathogen Pseudomonas savastanoi pv. savastanoi is dependent on the integrity of its GGDEF domain. Furthermore, deletion of the dgcP gene revealed that DgcP negatively regulates motility and positively controls biofilm formation in both the olive tree pathogen P. savastan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 109 publications
1
27
0
Order By: Relevance
“…Intriguingly, no differences were observed in the production of IAA or the expression of the T3SS in this strain, suggesting an additional and yet unknown bacterial factor contributing to knot development that is controlled by PleD. Another study demonstrated the role of DgcP, a conserved DGC in pseudomonads, in knot development by Psv NCPPB 3335 (Aragón et al, 2015b). A mutant in dgcP caused approximately a three-fold decrease in the size of knots induced in olive plants ( Figure 2 ) (Aragón et al, 2015b).…”
Section: Cyclic Di-gmp Levels Impact the Motile To Sessile Switch In mentioning
confidence: 81%
See 3 more Smart Citations
“…Intriguingly, no differences were observed in the production of IAA or the expression of the T3SS in this strain, suggesting an additional and yet unknown bacterial factor contributing to knot development that is controlled by PleD. Another study demonstrated the role of DgcP, a conserved DGC in pseudomonads, in knot development by Psv NCPPB 3335 (Aragón et al, 2015b). A mutant in dgcP caused approximately a three-fold decrease in the size of knots induced in olive plants ( Figure 2 ) (Aragón et al, 2015b).…”
Section: Cyclic Di-gmp Levels Impact the Motile To Sessile Switch In mentioning
confidence: 81%
“…Another study demonstrated the role of DgcP, a conserved DGC in pseudomonads, in knot development by Psv NCPPB 3335 (Aragón et al, 2015b). A mutant in dgcP caused approximately a three-fold decrease in the size of knots induced in olive plants ( Figure 2 ) (Aragón et al, 2015b). Furthermore, the lack of dgcP led to an altered motile/sessile phenotype compared with the wild-type strain; it exhibited increased swimming motility and decreased biofilm formation, likely through changes in exopolysaccharide production (Aragón et al, 2015b).…”
Section: Cyclic Di-gmp Levels Impact the Motile To Sessile Switch In mentioning
confidence: 99%
See 2 more Smart Citations
“…; Aragon et al . ), it is rarely found that GGDEF‐containing proteins inhibit the swimming motility through affecting flagellar biogenesis and assembly. Xoo harbours a single polar flagellum for motility with a flagella synthesis and control regulon of about 60 genes (Shen et al .…”
Section: Discussionmentioning
confidence: 99%